Watching over Yellowstone : The US Army's Experience in America's First National Park, 1886-1918 - Rust, Thomas C., 1969- (Book collections on Project MUSE., 2020)
"In 1883, Congress charged the US Army with managing Yellowstone National Park. The stability brought by the military was tangible, in spite of the soldiers' struggles with a job for which they were not trained in an environment that was hostile both physically and socially. While previous historians have looked at officers' letters and documents, providing a "top down" approach, Tom Rust examines the experience of common soldiers in the park. This "bottom up" social history provides a more complete picture of the army's experience in the park by highlighting the trials the soldiers faced, their successes, and the impact they had on developing the foundations for the National Park Service Ranger program"--